Evacuated tubes solar air collectors: a review on design configurations, simulation works and applications - Sulaiman, Nabila; Ihsan, Sany Izan; Syed Abu Bakar, Syed Noh; Abdul Majid, Zafri Azran; Zakaria, Zairul Azrul (Akademia Baru Publishing (M) Sdn Bhd, 2023)
One of the primary components of solar energy utilization systems is evacuated tube solar air collectors (ETSACs). The irradiance is absorbed by these collectors, which is then transformed into thermal energy at the absorbing surface before being transmitted to the air passing through the collectors. This type of collector outperforms flat plate collectors in terms of reducing heat loss through conduction and convection and also during cloudy days; thus, ETSACs are the most preferred collectors to be applied for space heating, crop drying, and industrial applications. This review focuses on a summary of design configurations, simulation works, and applications of ETSACs in order to understand the influence of the thermal performance of ETSACs so that these collectors can be applied more effectively. Studies on the use of nanofluids as thermal performance enhancers and phase change materials as thermal storage media can be considered to enhance the thermal performance of ETSACs.